Application of WEPP Hydrologic Simulation Model for Prediction of Rainfall and Runoff from Hilly Watersheds in Meghalaya - Singh, R K; Mishra, A K; Satapathy, K K (Journal of Agricultural Engineering, 2009)
In the present study, agriculture on the bench-terraced land was considered as one of the main alternatives to shifting cultivation. Considering the fact that most of the watersheds in the area are ungauged and sufficient database is lacking, modelling approach was adopted to quantify the soil erosion and runoff from the fields. Water Erosion Prediction Project (WEPP)-Watershed Model ver: 2002 was selected to describe the erosion processes on hill slopes considering its state-of-the-art technology. The model was reasonably calibrated based on a comparison between measured and simulated runoff for three land uses viz; shifting cultivation, agriculture with conservation measures and undisturbed natural vegetation. Calibrated model was run for event-based prediction of runoff and soil loss. The model over-predicted the small values of runoff and under-predicted the large values of runoff. Sensitivity analysis indicated that runoff was very sensitive to the Manning’s roughness coefficient, initial saturation level of the soil and effective hydraulic conductivity. Nash-Sutcliffe model efficiency (ME) and Root Mean Square Error (RMSE) ranged from 65 to 76% and 51.3 to 63.9, respectively, for all the three land uses. The conservation measures helped in reducing the sediment yield from 36.6 kg.ha?Â¹. mm?Â¹ of rainfall from shifting cultivation field to 8.6 kg.ha?Â¹.mm?Â¹. It can be inferred that the WEPP model can be used with reasonable accuracy, to simulate different management practices on hill slope for development and management planning of a hilly watershed.